Influence of milk, corn starch, and baking conditions on the starch digestibility, gelatinization, and fracture stress of biscuits - Conforti, Paula Andrea (2012)
Dough for nontraditional semisweet biscuits—prepared with wheat flour or replacing part of the wheat flour with corn starch, with or without skim milk—was baked at two oven temperatures, 120 or 170°C, until reaching moisture content and water activity lower than 6% and 0.5, respectively. Assays of fracture stress, differential scanning calorimetry, X‐ray diffraction, and starch digestibility were performed. Results showed that biscuits containing milk had the highest fracture stress, and biscuits baked at low temperature were harder than biscuits baked at high temperature. The degree of starch gelatinization during baking was higher when dough was baked at 170°C, compared with dough baked at 120°C. The decrease in gelatinization coincides with the decrease in the height and surface of peaks at 15 and 23° in the X‐ray diffraction patterns. Milk and corn starch did not affect the starch digestibility of biscuits, but biscuits baked at 170°C presented lower fracture stress and higher starch digestibility than biscuits baked at 120°C.